e-DEDALUS: A dynamic tool for data publishing on the web - Christos Bouras; Agis Konidaris; C Sintoris; A Apostolopoulos; V Khan (2000 International Conference on Information Society in the 21st Century-Emerging Technologies and new Challenges(IS 2000), Aizu-Wakamatsu City, Fukushima, Japan, 2000)
TheWorld WideWeb (WWW) provides a great opportunity for companies and individuals to publish their ideas, products and everything they would like other peo- ple to view. Since the Internet community and the Web are expanding every day, the demand for user friendly Web publishing applications is rising. The procedures that could be followed by Internet users in order to publish content on the web till now, were to either buy and read some books on HTML and have some basic knowledge on Web Servers, or pay an ISP a quite substantial amount of money to do it for them. In this paper we rst justify the necessity of the existence of an alternative method for online web pub- lishing. We then describe the method and a tool, called e-DEDALUS, which can be used by many diverse Internet user groups. An Internet user that has no previous expe- rience in programming, or desktop design, will be able to create his/her own Web site, online. The e-DEDALUS tool that will be described in this paper aims at oering simplic- ity, customisability and multilingual support to a substantial number of WWW users.